Comparison between Simple and Classical Techniques to Create Closed Pneumoperitoneum - Gharti, B. B.; Shrestha, P. M.; Shrestha, A.; Basnet, R. B.; Shah, C.; Adhikari, B. (Kathmandu University Medical Journal, 2021)
Background Closed method of pneumoperitoneum using Veress needle is an established technique. Classical closed technique is popular. Simple technique is a modified closed technique. Objective To compare the classical and simple techniques of closed pneumoperitoneum. Method This study was conducted in the department of urology, Bir hospital from August 1st 2019 to March 30th 2021. Total 114 patients were randomized into simple and classical technique of creating closed pneumoperitoneum. Time taken for creation of pneumoperitoneum, complications and failure of creating pneumoperitoneum in each group noted and analyzed. Chi square test, Fischer exact test and student t test were used and p < 0.05 considered significant. Result Among 114 patients, 61 in simple and 53 in classical technique allocated. In simple technique, mean age was 42.98±18.21 years, BMI was 21.84±2.57 kg/m2, mean time for pneumoperitoneum creation was 108.07±21.14 seconds. In classical technique, mean age was 40.15±17.58 years, BMI was 21.94±2.54 (kg/m2), mean time for pneumoperitoneum creation was 189.70±32.21 seconds. Mean time was less in simple technique than classical technique (p < 0.001). Complication rate observed was 6% in each technique (p=0.797) with cumulative rate of 10%. Omental injury was seen in 3.2% in simple technique and 5.6% in classical technique (p=0.662). Retroperitoneal insufflation was seen in 6.5% in simple technique and 5.6% in classical technique (p=0.842). No failed pneumoperitoneum was observed in both groups. Conclusion Simple technique is as effective, reproducible and safe method as classical technique of creating closed pneumoperitoneum.